Sirolimus Leads to Rapid Improvement in Fibroadipose Vascular Anomalies: Experience in 11 Children. Issue 4 (24th November 2021) - Al-Huniti, Ahmad; Fantauzzi, Michelle; Willis, Laura; Sadlier, Muriel; Amaral, Joao G.; Carcao, Manuel D.
Abstract : Purpose: Fibroadipose vascular anomaly (FAVA) is a complex vascular anomaly associated with postzygotic somatic PIK3CA mutations. FAVAs can cause significant pain, swelling, and musculoskeletal dysfunction. Treatment options are limited. Sirolimus is a well-tolerated and effective treatment for patients with FAVA. We report our experience of using sirolimus to treat 11 children with FAVAs. Methods: We conducted a retrospective review of all patients with FAVA treated with sirolimus in our institution. Results: Fourteen patients (10 females) were referred for sirolimus therapy for FAVA. Eleven patients were initiated on sirolimus at a mean age of 14 years (range: 9–17.9 years) and were then treated for a mean of 19 months (range: 1–46 months). Five had previously undergone sclerotherapy without benefit. Sirolimus was initiated at a dose of either 2.5 mg/m 2 once daily or 0.8 mg/m 2 twice daily. Doses were titrated to maintain sirolimus trough levels of 5–15 ng/L. Goals of treatment were improvement in pain and musculoskeletal dysfunction. All 11 patients reported reduced pain; 7 reporting this within 3 weeks of starting sirolimus. This allowed for discontinuation of analgesia. Function improved significantly in 9 of 11, leading to resumption of sports or work participation. Sirolimus side effects were similar to prior reports, most commonly mouth sores, mildly elevated lipids and acne. There was no grade III/IV toxicity. Conclusion: Sirolimus is a well-tolerated and effective treatment for patients with FAVA. Initial symptom improvement is rapid, with significantly reduced pain and improved function. We believe that sirolimus should be considered for all patients with FAVA as a first-line therapy before surgical/interventional approaches.